Analisis Yuridis Tentang Pembatalan dan Penolakan Keputusan Arbitrase Menurut Konvensi New York 1958 dan Implementasi di Indonesia dengan Undang-Undang Nomor 30 Tahun 1999 - Roza Nova, Sri Asih (Universitas Ekasakti, 2023)
Current economic developments have an impact on the public's lack of trust in their court institutions, where these court institutions are considered unprofessional, and not independent and even the moral integrity of judges in carrying out their profession has become blurred. Therefore, economic actors who really value time prefer alternative dispute resolution forums outside the court forum to resolve their business disputes which only require a short time and are in line with their business spirit. One of the alternative dispute resolution forums that is widely chosen and most popular among business people is arbitration. Decisions issued by this arbitration body are final and binding, but these decisions can be canceled and rejected as regulated in the 1958 New York Convention and implemented by Indonesia with Law No. 30 of 1999. Therefore, in this research, researchers will analyze how to regulate the annulment and rejection of arbitration decisions based on the two provisions mentioned above. To answer the questions in this research, the author uses normative juridical research methods. The research process will explore data in the form of legal provisions that have been written and are still in effect, as well as forms of information that have been published and the results of the analysis are described using qualitative methods, namely data acquisition methods, data organization. , sorting them into manageable units, synthesizing them, looking for and finding patterns, finding out what is important and what is learned, and deciding what can be used to answer the problem. From this research, the answer was found to be that both the 1958 New York Convention and Law No. 30 of 1999 do not concretely regulate the annulment of arbitration awards, but both regulations allow for the annulment of arbitration awards if they fulfill the requirements. Regarding the rejection of arbitration decisions, it is regulated concretely in article V of the 1958 New York Convention, as well as Law No. 30 of 1999, which also regulates concretely in article 66 letter c.